Gag proteins of the highly replicative MN strain of human immunodeficiency virus type 1: posttranslational modifications, proteolytic processings, and complete amino acid sequences. - Henderson, L E (1992)
The MN strain of human immunodeficiency virus type 1 was grown in H9 cells, concentrated by centrifugation, and disrupted, and proteins were purified by reversed-phase high-pressure liquid chromatography. Complete amino acid sequences were determined for the mature Gag proteins, showing natural proteolytic cleavage sites and the order of proteins (p17-p24-p2-p7-p1-p6) in the Gag precursors. At least two sequence variants of p24 and eight sequence variants of p17 were detected. The two most abundant variants of p24 and p17 represented at least 50% +/- 5% and 20% +/- 5% of their totals, respectively. These data suggest heterogeneity in the virus population, with 50% of the total virus containing the most abundant forms of p17 and p24 and 20% of the virus containing the second most abundant forms. The Gag precursors of these suggested viruses differ from each other by only 3 amino acid residues but differ from the precursors predicted by the published MN proviral DNA sequence by 10 residues. Electrospray ionization mass spectrometry analysis of the purified p24 forms showed that the measured molecular weight of the protein was 200 +/- 50 atomic mass units greater than the calculated molecular weight. The source of additional mass for the p24 forms was not determined, but the observation is consistent with previous suggestions that the protein is phosphorylated. Greater than 98% of the total recovered p17 was myristylated at the N-terminal glycine residue, and the measured molecular weights (as determined by electrospray ionization mass spectrometry) of the most abundant forms were within 3 atomic mass units of the calculated molecular weights (15,266).